Mafic dykes from the Perhentian Islands: subdivision and preliminary textural and geochemical study - Azman Abdul Ghani, (Universiti Kebangsaan Malaysia, 2002)
Mesozoic mafic dykes in the Perhentian islands and their surrounding area can be divided into two based on their field occurrence, i.e. the older and younger dykes. The older dykes are synplutonic to their felsic host and the younger dykes post date their felsic host. Synplutonic features shown by the older dykes are recrystallisation of the dyke with the production of amphibolite or hornfelsic texture, back veining into the dyke and dismemberment of the dyke into trains of ameboid enclaves. All these features suggest that hot mafic dyke magma intruded into mobile semi solid felsic magma. The younger dykes, which are more abundant, are mainly doleritic in composition and are similar to those found throughout the Eastern Belt of Peninsular Malaysia. They are made up of plagioclase, clinopyroxene, amphibole, iron ore and chlorite. Geochemical study shows that the younger dykes formed in a continental environment within plate tectonic setting.